Defining America at the Border: The Line Riders of the Mexican Border District, 1892-1924 - Dupree, James Jr. (My University, 2019)
Defining America at the Border: The Line Riders of the Mexican Border District, 1892-1924 is the story of the line riders. Also known as Immigrant Inspectors, the Mounted Guard (both with the Bureau of Immigration), and Chinese Inspectors (with the Customs Service) the line riders were the precursors of the Border Patrol. The line riders were a manifestation of the attempt to define national identity by the United States government by controlling who was allowed to cross the Mexican border into the United States. They pursued the goals of nativists and supporters of immigration restriction as the country fitfully transitioned from the frontier era into the Gilded Age and then the Progressive Era. National ideologies played out along the border just as they did nationwide. Examining the border from 1894 to 1924 provides a fuller understanding of the growth of the Nation State by showing how that growth occurs at the ground level. The line riders were the first federal, militarized, armed police force along the Mexican border, predating the Border Patrol by thirty years as well as any border wall or fence. The border enforcement apparatus was fully realized as a result of the move towards efficiency by Progressive Era bureaucrats. Through the actions of the line riders, America’s border with Mexico first became a tangible obstacle for immigrants, and a defining entity for Americans.
Keywords: Border; Borderlands; immigration service; Bureau of Immigration; immigration; Border Patrol; line riders; nation building; state building; Mexican border; Greater Reconstruction; Gilded Age; Progressive Era; progressivism; progressives; Nation State; bureaucracy; border enforcement; citizenship